Resveratrol solid lipid microparticles as dry powder formulation for nasal delivery, characterization and in vitro deposition study. (16th November 2016) - Martignoni, Isabella; Trotta, Valentina; Lee, Wing-Hin; Loo, Ching-Yee; Pozzoli, Michele; Young, Paul M.; Scalia, Santo; Traini, Daniela
Abstract: This study focuses on development and in vitro characterisation of a nasal delivery system based on uncoated or chitosan-coated solid lipid microparticles (SLMs) containing resveratrol, a natural anti-inflammatory molecule, as an effective alternative to the conventional steroidal drugs. The physico-chemical characteristics of the SLMs loaded with resveratrol were evaluated in terms of morphology, size, thermal behaviour and moisture sorption. The SLMs appeared as aggregates larger than 20 μm. In vitro nasal deposition was evaluated using a USP specification Apparatus E 7-stage cascade impactor equipped with a standard or a modified nasal deposition apparatus. More than 95% of resveratrol was recovered onto the nasal deposition chamber and stage 1 of impactor, suggesting that the SLMs mostly deposited in the nasal cavity. Additionally, the SLMs were not toxic on RPMI 2650 nasal cell line up to a concentration of approximately 40 μM of resveratrol.